Enhancing Community Education in Tumbang Tahai as an Effort to Manage Long-tailed Monkey Conflict and Zoonosis (Macaca fascicularis) in Settlements - Titin Purnaningsih; Rahayu Opi Anggoro; Decenly Decenly; Rizka Hasanah (Universitas Lambung Mangkurat, 2024)
The conflict between Long-tailed Monkeys and the villagers of Tumbang Tahai Village is a significant issue that must be addressed. Two hundred long-tailed monkeys colonies have infiltrated communities, causing damage and disruption to the facilities of the villagers. It is widely acknowledged that enhancing community education is critical in addressing the challenges afflicting Tumbang Tahai Village. This activity aims to enhance the knowledge and understanding of the villagers of Tumbang Tahai Village regarding managing and resolving conflicts with long-tailed monkeys, including strategies for responding to bites or assaults and initiatives to reduce conflict. Residents of RT 3 / RW 1 Tumbang Tahai Village, Bukit Batu District, Palangka Raya City, Central Kalimantan, comprised the implementing partners. The method utilised in Community Service is Participatory Action Research (PAR), which aims to empower community members to become agents of change through knowledge acquisition. On Wednesday, October 25, 2023, community service activities were conducted at the SDN 03 Tumbang Tahai. These activities consisted of multiple stages: observation, preparation, implementation, and evaluation. Activities include distributing materials on conflict prevention and the risk of zoonotic transmission, discussion, seed distribution for monitoring purposes, and assessment via surveys, pre-tests, and post-tests. The evaluation results demonstrated a discernible enhancement in knowledge after the training. On average, the post-test score rose from 51% on the pre-test to 97.5%. This indicates that the participants' understanding of conflict resolution and zoonotic improved after their participation in the socialisation program.